The Influence of Experiential Marketing, Brand Image and Location on Repurchase Intention in Lapau Kapau - Dona Amelia; Febriana, Ayu (Adpebi Science Series, 2024)
This research aims to analyze Experiential Marketing on Repurchase Intention at Lapau Kapau. To analyze Brand Image on Repurchase Intention at Lapau Kapau . The research uses quantitative methods. The type of data in this study is primary data by distributing questionnaires to all visitors of Lapau Kapau . The sampling technique uses Probability sampling, which is a sampling technique carried out by giving equal opportunities in the population to be selected as a sample. The analysis technique uses test tools with the help of SmartPLS software version 3. Based on the results of the hypothesis testing that have been described in the research results, it shows that: (1) experiential marketing is known to have a positive but not significant effect on repurchase intention on consumers who want to visit Lapau Kapau . (2) Brand image is known to have a positive and significant influence on repurchase intention on consumers who want to visit Lapau Kapau . (3) Location is known to have a positive and significant influence on repurchase intention on consumers who want to visit Lapau Kapau .